Evaluation of Gentamicin and Lidocaine Release Profile from Gum Acacia-crosslinked-poly(2-hydroxyethylmethacrylate)-carbopol Based Hydrogels - Singh, Baljit; Dhiman, Abhishek (Current Drug Delivery, 2017)
Background: No doubt, the prevention of infection is an indispensable aspect of the wound management, but, simultaneous wound pain relief is also required. Therefore, herein this article, incorporation of antibiotic agent ‘gentamicin’ and pain relieving agent ‘lidocaine’ into hydrogel wound dressings, prepared by using acacia gum, carbopol and poly(2-hydroxyethylmethacrylate) polymers, has been carried out. The hydrogels were evaluated as a drug carrier for model drugs gentamicin and lidocaine. Method: Synthesis of hydrogel wound dressing was carried out by free radical polymerization technique. The drug loading was carried out by swelling equilibrium method and gel strength of hydrogels was measured by a texture analyzer. Results: Porous microstructure of the hydrogel was observed in cryo-SEM images. The hydrogel showed mesh size 37.29 nm, cross-link density 2.1910-5 mol/cm3, molecular weight between two cross-links 60.2510-3 g/mol and gel strength 0.625±0.112 N in simulated wound fluid. Conclusion: It is concluded that the pH of swelling medium has influenced the network structure of hydrogel i.e., molecular weight of the polymer chain between two neighboring cross links, crosslink density and the corresponding mesh size. A good correlation was established between gel strength and network parameters. Cryo-SEM images showed porous morphology of hydrogels. These hydrogels were found to be biodegradable and antimicrobial in nature. Drug release occurred through Fickian diffusion mechanism and release profile was best fitted in first order model. Overall it is concluded that modification in GA has led to formation of a porous hydrogels for wound dressing applications.
Keywords: gel strength